2013
DOI: 10.3758/s13423-013-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Speaking order predicts memory conformity after accounting for exposure to misinformation

Abstract: When people discuss their experiences, they can later report seeing things that they never saw, simply because they heard about those things in the discussion. One factor that may contribute to this effect is the order in which people speak; some research has investigated this issue, but it remains unclear whether a relationship exists between memory conformity and speaking order. We explored this question using data from five previous memory conformity experiments. The results provide evidence of an associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The effect of social influence was still present, however. Many other studies confirmed that misinformation delivered in a social interaction is effective (e.g., Dalton & Daneman, 2006;Gabbert et al, 2003;Hewitt, Kane, & Garry, 2013;Luus & Wells, 1994;Mudd & Govern, 2004;Numbers, Meade, & Perga, 2014;Oeberst & Seidemann, 2014;Schneider & Watkins, 1996;Wright et al, 2000).…”
mentioning
confidence: 86%
“…The effect of social influence was still present, however. Many other studies confirmed that misinformation delivered in a social interaction is effective (e.g., Dalton & Daneman, 2006;Gabbert et al, 2003;Hewitt, Kane, & Garry, 2013;Luus & Wells, 1994;Mudd & Govern, 2004;Numbers, Meade, & Perga, 2014;Oeberst & Seidemann, 2014;Schneider & Watkins, 1996;Wright et al, 2000).…”
mentioning
confidence: 86%
“…For example, Gabbert et al (2004) found that young and old participants were more mislead by misinformation shared directly by a confederate (social misinformation) than by indirect misinformation (non‐social misinformation). Several other studies have shown that discussing the shared experience can lead witnesses to include information reported by a co‐witness in their own memory reports (Gabbert et al, 2003; Garry et al, 2008; Hewitt et al, 2013; Hope et al, 2008; Ito et al, 2019; Kanematsu et al, 1996/2003; Paterson & Kemp, 2006). This co‐witness suggestibility effect has been found with different experimental procedures.…”
Section: Figurementioning
confidence: 99%
“…In contrast, participants rely on information more from partners with whom they have a prior relationship (e.g., friends or romantic partners) than from strangers (French, Garry, & Mori, ; Hope, Ost, Gabbert, Healey, & Lenton, ), presumably because of perceived reliability. Perception of power also plays a role; for example, individuals are more likely to incorporate information received from those perceived to have more power in certain relationship dynamics (Skagerberg & Wright, ; but see Carol, Carlucci, Eaton, & Wright, ; Skagerberg & Wright, ), those with a competitive rather than cooperative mindset (Park, Son, & Kim, ), those who speak first (Gabbert, Memon, & Wright, ; Hewitt, Kane, & Garry, ; Wright & Carlucci, ), and those asserting more confidence (Allan & Gabbert, ; Wright et al., ). Finally, personality and emotional factors such as social avoidance (Wright, London, & Waechter, ), increased openness, extraversion, and neuroticism are associated with reduced social contagion, whereas increased agreeableness is associated with greater social contagion (Doughty, Paterson, MacCann, & Monds, ).…”
Section: Social Transmission Of False Memories In Small Groupsmentioning
confidence: 99%